Randomized trial of Macitentan/Tadalafil single-tablet combination therapy for pulmonary arterial hypertension - Grünig, Ekkehard; Jansa, Pavel; Fan, Fenling; Hauser, Jakob A.; Pannaux, Matthieu; Morganti, Adele; Rofael, Hany; Chin, Kelly M. (Journal of the American College of Cardiology, 2024)
Background - Endothelin receptor antagonist (ERA) and phosphodiesterase 5 inhibitor (PDE5i) combination therapy is recommended for low-/intermediate-risk pulmonary arterial hypertension (PAH) patients. A fixed-dose combination of the ERA macitentan and PDE5i tadalafil (M/T FDC) in a once-daily, single tablet would simplify treatment. - Objectives - The multicenter, double-blind, adaptive phase 3 A DUE study investigated the efficacy and safety of M/T FDC vs macitentan 10 mg and vs tadalafil 40 mg monotherapies in PAH patients, including treatment-naïve and prior ERA or PDE5i monotherapy-treated patients. - Methods - World Health Organization functional class II-III patients were randomized to M/T FDC, macitentan, or tadalafil depending on their PAH treatment (treatment-naïve, ERA, or PDE5i monotherapy) at baseline. The primary endpoint was change in pulmonary vascular resistance (PVR) at week 16. - Results - In total, 187 patients were randomized to single-tablet M/T FDC (n = 108), macitentan (n = 35), or tadalafil (n = 44). PVR reduction with M/T FDC was significantly greater vs macitentan (29%; geometric mean ratio 0.71; 95% CL: 0.61-0.82; P < 0.0001) and vs tadalafil (28%; geometric mean ratio 0.72; 95% CL: 0.64-0.80; P < 0.0001). Three patients died in the M/T FDC arm (judged unrelated to treatment). Adverse events (AEs) leading to discontinuation, serious AEs, and those of special interest (anemia, hypotension, and edema) were more frequent with M/T FDC. - Conclusions - Macitentan and tadalafil FDC significantly improved PVR vs monotherapies in PAH patients, with a safety and tolerability profile consistent with the individual components. The A DUE study supports M/T FDC as a once-daily, single-tablet combination for initial therapy and escalation to double combination therapy in patients with PAH. (Clinical Study to Compare the Efficacy and Safety of Macitentan and Tadalafil Monotherapies With the Corresponding Fixed-dose Combination Therapy in Subjects With Pulmonary Arterial Hypertension [PAH]) [A DUE]; NCT03904693)
Online verfügbar: 22. Januar 2024
Gesehen am 02.08.2024